Penerapan Model Problem Based Learning Berbantuan Media Konkret untuk Meningkatkan Hasil Belajar Matematika Kelas II SD 1 Kalirejo - Prasida, Hesti Widya; Fardani, Much Arsyad; Sudjadi, Sudjadi (Lembaga Yasin AlSys, 2025)
The purpose of this study is to improve the mathematics learning outcomes of second-grade students at SD 1 Kalirejo on the topic of time measurement using the Problem Based Learning model supported by concrete media in the form of a time board. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The subjects of the study are second-grade students in the even semester of the 2024/2025 academic year, totaling 30 students, comprised of 19 boys and 11 girls. Cycle I and Cycle II each took place over three meetings. The results indicate an improvement in the average score of students from 58 in the pre-cycle to 70.07 in Cycle I, and reaching 82.43 in Cycle II. The percentage of classical completeness also increased from 43.33% in the pre-cycle to 66.67% in Cycle I, and reaching 80% in Cycle II. In addition to improving learning outcomes, the application of the PBL model also positively impacted students' active participation, critical thinking skills, and teamwork. The utilization of concrete media in the form of a time board facilitated students' understanding of the concept of time visually and tangibly, which is appropriate for their cognitive development level. The results of this study confirm that the application of the Problem Based Learning model assisted by concrete media has been proven effective in enhancing mathematics learning outcomes for students at the elementary school level.